ANALYSIS AND OPTIMIZATION OF FRICTION WELDING PARAMETERS FOR AA6061-AA2014 DISSIMILAR JOINTS - Mathi, K.; Jinu, G.R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Friction welding is a solid state welding used owing to its properties such as low heat input, high production efficiency and environment friendliness. Materials which aredifficult towelded by fusion welding processes can be successfully done friction welding. In this work, an effort was made to predict the maximum tensile strength of friction welded AA 6061 and AA 2014 aluminium alloy dissimilar joints incorporating the process parameters such as rotational speed, friction pressure and forging pressures which have immense on the strength of joints. The friction welding process parameters were optimized to achieve maximum tensile strength of the joint. The maximum tensile strength of 210MPa Â for the joints fabricated under the welding conditions ofrotational speed 1508 rpm, friction pressure of 8.16 MPa/secand forging pressure of 6.79 MPa/sec using the optimization techniques.